Titanium plate fixation of flail chest - Muhammad Nadeem; Hibbut-; William F. Stendardi; Kathryn D. Bass (Elsevier, 2018)
Introduction: We present short and long term outcomes of titanium rib plating in two pediatric patients with traumatic flail chest. Cases: Patient 1 is a 12 year old male ATV driver with left thorax handlebar impalement with a flail segment of ribs 4-8. He was unable to wean from the ventilator by hospital day (HD) 4 and had titanium plating of ribs 4-7. He was extubated on postoperative day (POD) 1 and discharged home on POD 5. He returned to contact sports at 6 months. Patient 2 is a 13 year old male dirt bike rider with fractures of left ribs 8-12, including a 9-10 flail segment. He was unable to wean from the ventilator by HD 3 and had titanium plating of ribs 8-10. He was extubated on POD 2 and discharged on POD 11. After 4 months of therapy, he returned to full activity. Conclusions: In these two patients, flail chest resulted in failure to wean from the ventilator. Plating of the flail segment allowed ventilator weaning, improved pain control, and return to normal activity with minimal symptoms. Long-term outcomes show excellent cosmetic and functional results with symmetric chest wall growth (Table 1) Level of evidence: IV.